7x+9=10x+(-3+3x)

Simple and best practice solution for 7x+9=10x+(-3+3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+9=10x+(-3+3x) equation:


Simplifying
7x + 9 = 10x + (-3 + 3x)

Reorder the terms:
9 + 7x = 10x + (-3 + 3x)

Remove parenthesis around (-3 + 3x)
9 + 7x = 10x + -3 + 3x

Reorder the terms:
9 + 7x = -3 + 10x + 3x

Combine like terms: 10x + 3x = 13x
9 + 7x = -3 + 13x

Solving
9 + 7x = -3 + 13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13x' to each side of the equation.
9 + 7x + -13x = -3 + 13x + -13x

Combine like terms: 7x + -13x = -6x
9 + -6x = -3 + 13x + -13x

Combine like terms: 13x + -13x = 0
9 + -6x = -3 + 0
9 + -6x = -3

Add '-9' to each side of the equation.
9 + -9 + -6x = -3 + -9

Combine like terms: 9 + -9 = 0
0 + -6x = -3 + -9
-6x = -3 + -9

Combine like terms: -3 + -9 = -12
-6x = -12

Divide each side by '-6'.
x = 2

Simplifying
x = 2

See similar equations:

| 2x+3y+5z=120 | | 79-5(3x+7)=14 | | -2z=-6+4z | | 2+3j=10+4j | | 4(v-2)=4v+8-2(-4v-1) | | 5(f-5)=25 | | -5(u+2)=-2(5u-2)+9u | | 26=14ln(2.5x+5) | | X/10-5=1 | | 12x^3/4x^2= | | 7y-15=3x | | -3(y+2)=-6y+21 | | p=a+2+3 | | 5+2.3y=x | | -2u-17=-5(u+4) | | 10(s-9)=-114 | | 5x+18=2x+12 | | x=5+2.3y | | 10(s-9)=114 | | 2q=9q+7 | | 5k=-7+4k | | 4x+16=3x+6 | | 2x11/5 | | 3x=7y-15 | | -2g=-3g+6 | | -8m=-10m+10 | | 6p+10=7p | | -21/7x=20/21 | | 2sin(x-30)=1 | | -10x-4=-6 | | 2(x+7)+23=9-3(x-1) | | -10+9d=8 |

Equations solver categories